THE IMPLEMENTATION OF STRATEGY BASED ON COMPANY STRATEGY AND MICRO BUSINESS ENVIRONMENT TO ACHIEVE BUSINESS PERFORMANCE FOR SMALL AND MEDIUM BUSINESS IN WEST JAVA, INDONESIA DURING COVID-19 PANDEMIC - Hermina, Nurul; Sinaga, Obsatar; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
It has been more than one year's pandemic COVID-19 poses a threat not only to public health but also has a very serious social and economic impact. Many businessmen were forced to close their businesses due to low public buying interest, declining sales and capital difficulties. One of the most affected is the small and medium business sector in Indonesia, especially West Java as one of the provinces with the largest number of SME business players. The pandemic has not shown any signs of ending but the economy must continue to run to sustain people's lives. This research was conducted with the aim at finding the most effective formulation to improve SME business performance during the pandemic by digging up information on whether the company's strategy and the micro external environment have a positive impact on business performance through strategy implementation. The research conducted using a survey method using the structural equation modeling partial least square (SEM-PLS) analysis technique, with a sample of 138 respondents from Small and Medium Enterprises in West Java. The results of the analysis found that there was a significant effect of the company's strategy variables and the micro external environment on business performance through strategy implementation, as well as the micro external environment covering aspects of competition and customer needs, which are factors that must be prioritized by SMEs to encourage business performance growth.